1999
DOI: 10.1038/sj.onc.1203052
|View full text |Cite
|
Sign up to set email alerts
|

Testicular wild-type p53 expression in transgenic mice induces spermiogenesis alterations ranging from differentiation defects to apoptosis

Abstract: While p53 is dispensable for development, an excess of p53 has dramatic consequences on the embryogenesis and on the cell dierentiation. In an attempt to analyse in vivo the eects of p53 activity, we have generated transgenic mice expressing the wild-type p53 under the control of the metallothionein I promoter. In the three transgenic lines established, exogenous p53 is expressed constitutively in the postmeiotic cells of transgenic males and two lines are subfertile. Transgenic males expressing the upper leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 58 publications
4
30
0
1
Order By: Relevance
“…Spermatocytes II and spermatids from MTp53 males express p53 and undergo cell death Our previous immunohistological results (Allemand et al 9 and supplementary file 1) show that ectopic p53 is present in the round spermatids of MTp53 testis. Nevertheless, in adult spermatogenesis, the MTI promoter is constitutively activated from the pachytene stage of meiosis.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Spermatocytes II and spermatids from MTp53 males express p53 and undergo cell death Our previous immunohistological results (Allemand et al 9 and supplementary file 1) show that ectopic p53 is present in the round spermatids of MTp53 testis. Nevertheless, in adult spermatogenesis, the MTI promoter is constitutively activated from the pachytene stage of meiosis.…”
Section: Resultsmentioning
confidence: 71%
“…The tissue was further rinsed once in PBS, fixed for 12 h in 4% paraformaldehyde-PBS and wax-embedded. TUNEL was performed as described previously 9 and tubules were scored for the presence of labeled cells (7S.E.). At least two transgenic testes per set of conditions were used with their normal counterpart.…”
Section: Ex Vivo Inhibition Assay Of Caspase and Calpain Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study indicated that overexpressed wild-type p53 was in a latent form in F9 murine teratocarcinoma, suggesting a lack of selective pressure to mutate p53 in TGCTs (Lutzker and Levine, 1996). Transgenic mice homologously deleted for p53 have a high incidence of spontaneous testicular cancer and targeted over-expression or miss-expression of p53 in mice results in defects in spermiogenesis (Harvey et al, 1993;Schwartz et al, 1999;Allemand et al, 1999). This, coupled with the fact that p53 expression is restricted to the pachytene stage of meiosis, has led Chaganti and colleagues to propose that the near tetraploid TGCT arises from a meiotically arrested pachytene spermatocyte, which has been aberrantly driven to initiate mitotic cell division (Chaganti and Houldsworth, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, unregulated expression might even limit the generation of the mouse lines. For instance, efforts to generate p53 transgenic mice repeatedly failed due to severe defects in embryogenesis, differentiation and apoptosis (Nakamura et al, 1995, Godley et al, 1996, Allemand et al, 1999. In contrast to classical transgenic vectors, bacterial artificial chromosomes (BAC) can harbor up to 300kb of DNA and can accommodate full genes along with their regulatory elements (Shizuya et al, 1992).…”
Section: Transgenesismentioning
confidence: 99%